2008
DOI: 10.1111/j.1556-4029.2008.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Detection of Deception After Committing a Mock Sabotage Crime*

Abstract: Using Blood Oxygen Level Dependent (BOLD) functional MRI (fMRI) to detect deception is feasible in simple laboratory paradigms. A mock sabotage scenario was used to test whether this technology would also be effective in a scenario closer to a real-world situation. Healthy, nonmedicated adults were recruited from the community, screened, and randomized to either a Mockcrime group or a No-crime group. The Mock-crime group damaged and stole compact discs (CDs), which contained incriminating video footage, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 24 publications
(40 reference statements)
2
10
0
Order By: Relevance
“…A 2 (belief: “lie-detector” on, “lie-detector” off) × 2 (question type: theft-related truth-eliciting, theft-related falsehood-eliciting) repeated-measures ANOVA revealed no main effects [belief: F (1, 16) = 0.169, p = 0.69; question type: F (1, 16) = 0.00, p = 0.97], and no interaction between belief and question type [ F (1, 16) = 2.381, p = 0.142; see Figure 2]. The similarity between the RTs evoked by questions in the different conditions calls into question previous reports (e.g., Nuñez et al, 2005; Abe et al, 2007; Kozel et al, 2009), which suggested that RTs could be used to distinguish deceptive and truthful behavior (but see the Discussion, where we note the limitations of using RTs in the present context).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…A 2 (belief: “lie-detector” on, “lie-detector” off) × 2 (question type: theft-related truth-eliciting, theft-related falsehood-eliciting) repeated-measures ANOVA revealed no main effects [belief: F (1, 16) = 0.169, p = 0.69; question type: F (1, 16) = 0.00, p = 0.97], and no interaction between belief and question type [ F (1, 16) = 2.381, p = 0.142; see Figure 2]. The similarity between the RTs evoked by questions in the different conditions calls into question previous reports (e.g., Nuñez et al, 2005; Abe et al, 2007; Kozel et al, 2009), which suggested that RTs could be used to distinguish deceptive and truthful behavior (but see the Discussion, where we note the limitations of using RTs in the present context).…”
Section: Resultssupporting
confidence: 50%
“…To examine whether the belief that a “lie-detector” was active affected participants' production of deceptive responses, we examined reaction time (RT) data (Nuñez et al, 2005; Abe et al, 2007; Kozel et al, 2009). RTs were calculated as the duration from the end of a question to the participant's button response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies found that the prefrontal-parietal and anterior cingulate cortices, as the executive brain regions, are pivotally involved in deception [10][17]. However, because of the nonspecific relationship between deception and these executive regions, sufficient accuracy has not been obtained with the use of these executive regions to discriminate the guilty from the innocent [18]. Many publications in this area have pointed out this disadvantage [19][21], and some researchers believe that it is difficult to find a simple biological marker that can indicate deception, as this is a highly complex and multifaceted cognitive process.…”
Section: Introductionmentioning
confidence: 99%